Kajian Perancangan Rumah Sederhana Berkonsep Klimatik pada Kampung Dempet di Tipar Padalarang Bandung - Margareta Maria Sudarwani; Sally Septania; Jessica Miracella Indry; Gabrielle Charles Jourdan (Universitas Sebelas Maret Surakarta, 2024)
Climatic architecture is becoming a popular concept as it addresses issues of climate change, economy, and building health. The pandemic has heightened awareness of the importance of cross-ventilation, bringing the climatic concept back into focus for the design of new buildings and the development of existing ones. This study aims to: 1) Identify the characteristics of urban village houses with attached homes focused on thermal comfort, 2) Determine climatic design criteria for attached houses, 3) Understand the application of climatic concepts in attached houses. The methodology used is descriptive quantitative, with data from field conditions and references from journals. The results indicate that in addition to window placement aligned with wind direction, the use of wind chimneys and rain harvesting systems can be implemented in houses in densely built villages. This research is expected to provide knowledge about climatic architecture and offer solutions for its application in contemporary building design.